MONITORING THE IMPACT ON THE PERFORMANCE OF EMPLOYEES IN RB SAMBAS ARTA (Study at BPR SAMBAS ARTA ) - B31111151, TIWI EKA NURINDAH SARI (Jurnal Manajemen Update, 2016)
The impact of supervision on employee performance becomes very important . because supervision is conduct management activities in observation of human resources in the organization . supervision consisting of active and passive surveillance . The objective of this study to determine the effect of passive surveillance on employee performance . object of this study are employees of BPR Sambas Arta . Data collection is done by distributing questionnaires to 30 respondents . data analysis was performed using SPSS 17. based on the results of research conducted active surveillance was found to have a significant influence on the performance of employees amounted to 3.689 . Passive surveillance has a significant influence on the performance of employees amounted to 2,995 . Key words : Active and Passive Monitoring ,Â  Employee Performance